Anxiety and related factors among mothers of postoperative pediatric patients at King Chulalongkorn Memorial Hospital - Yordsawat, Yadaporn; Roomruangwong, Chutima; Rajatapiti, Prapapan (Chulalongkorn Medical Journal, 2022)
Background: According to previous studies, mothers caring for children with various diseases had anxiety. However, few studies were conducted on anxiety and related factors among mothers of postoperative pediatric patients in Thailand. Objectives: To study the prevalence of anxiety and related factors among mothers of postoperative pediatric patients at King Chulalongkorn Memorial Hospital. Methods: Data were collected from 105 mothers of pediatric patients receiving corrective surgery as in-patients and out-patients by using questionnaires including: 1) The mothers’ demographic questionnaire; 2) The children’s background questionnaire; 3) The STAI Form-Y1, Y2 anxiety measuring form; and, 4) The Parental Stress Scale: Pediatric Intensive Care Unit (PSS: PICU). Univariate analysis (t - test and Chi-square) was used to examine the factors related to anxiety and multivariate analysis was used to determine the predictors of anxiety among this group of mothers. Results: Most mothers had moderate level of anxiety state (63.5%) and moderate level of anxiety trait (53.3%). Among them, 3.8 % had high anxiety state, whereas 6.7% had high anxiety trait. Four factors were found correlated with anxiety: having more than four family members, children undergone major surgery, having moderatesevere anxiety trait and having stress from children’s behavioral and emotional response. Conclusion: On average, the subjects had moderate level of anxiety. Associated factors to anxiety were number of family members, major surgery, moderate-severe anxiety trait, and stress from children’s behavioral and emotional responses. These results suggested the medical staffs to help mothers decrease their anxiety level and to encourage them to support the treatment of their children.